Peran Strategis Wanita dalam Keluarga dan Pengelolaan Keuangan Rumah Tangga pada Agroindustri Ikan Asin di Kabupaten Tulang Bawang - Abdurrokhim, Muhammad; Setiawati, S. Bherliana Maharani; Triandini, Puja; Sigiro, Yudika Ester Kejutini; Safitri, Yuli (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study aims to analyze the role of women in family activities and family financial management within households engaged in the salted fish agroindustry in Tulang Bawang Regency. The research employed a descriptive method with a quantitative approach, utilizing primary data collected through interviews and questionnaires with women involved in salted fish processing. The results indicate that women play a significant role in family activities, encompassing domestic, social, and production aspects. In family financial management, women’s involvement is more dominant than that of men, with an average contribution of 15.44% independently and 25.73% in joint activities dominated by women, while activities conducted jointly without dominance reached 48.12%. Male involvement remains relatively low, at 9.65% in joint activities dominated by men and 1.07% independently. These findings highlight that women hold a central position in planning, organizing, implementing, and evaluating family finances, which supports household economic stability and the sustainability of home-based agroindustrial enterprises.